2022
DOI: 10.3390/fishes7040146
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Interlocation Sexual Shape Dimorphism in Caquetaia kraussi (Perciformes: Cichlidae): A Geometric Morphometric Approach

Abstract: C. kraussii is an endemic fish species from Colombia and Venezuela and represents a valuable food resource for local human communities. Due to its economic importance, the management and captive breeding of this species are of special interest. However, the anatomical similarities between sexes have been a problem for visual identification. It is also important to indicate that C. kraussii has cryptic morphological behavior between sexes, a topic that has been one of the main problems for the implementation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…The PLS analysis indicated that about 90% of the variation in body shape explained by PC1 was not due to the environmental variables measured. This agrees with the results of Hernández et al, 2022, which show marked sexual dimorphism, suggesting that the body shape of males of C. kraussii is more conserved, submitted mostly to sexual selection pressures, while the body shape of females appears to be affected by environmental pressures, from which it may be inferred that most body shape variation is subject to sexual selection [ 39 ]. By contrast, PC2 and PC3, which together explained about 10% of the body shape variation, are mostly (≈90%) determined by the dissolved oxygen and the T°-pH combination, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The PLS analysis indicated that about 90% of the variation in body shape explained by PC1 was not due to the environmental variables measured. This agrees with the results of Hernández et al, 2022, which show marked sexual dimorphism, suggesting that the body shape of males of C. kraussii is more conserved, submitted mostly to sexual selection pressures, while the body shape of females appears to be affected by environmental pressures, from which it may be inferred that most body shape variation is subject to sexual selection [ 39 ]. By contrast, PC2 and PC3, which together explained about 10% of the body shape variation, are mostly (≈90%) determined by the dissolved oxygen and the T°-pH combination, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Photographs were taken with a high-resolution FUJIFILM X-T2 24-megapíxel camera; TPS programs was used to transform the photos to TIF format [ 46 ]. Fifteen landmarks were digitized using Hernandez et al [ 39 ]’s landmark map for Caquetaia kraussii ; they are illustrated in Figure 2 . The landmarks were digitalized and transformed to two-dimensional coordinates using the software tpsDig2 [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding and classifying the complexity of fish diversity and other organisms have historically been on the basis of comparative morpho‐anatomical characteristics. Part of this diversity may be established by natural and/or sexual selection (Hernandez et al, 2022). Based on the sexual selection theory, selection provides reproduction advantages to individuals of the same species and sex and affects the success of differential mating (Andersson, 1994; Hernandez et al, 2022; Lima‐Filho et al, 2017; Rodríguez et al, 2005).…”
Section: Introductionmentioning
confidence: 99%